INTERNET TECHNOLOGIES IN TEACHING THE RUSSIAN LANGUAGE IN NATIONAL SCHOOLS (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
The authors of this article teach in Russian new ways of developing conversational speech with the help of the Internet to students in schools that have given a significant understanding of the methods.